Register Now

222-9+11+12:2*14+14 = ? ( )

Toán Lớp 8: Tìm x 1, x(1-2x)+(x-2)(2x-3)=0 2, (x-1)(x+2)-x-2=0 3, x^3-16x=0 4, (2x-3)^2+(x-3)(3-2x)=0

Toán Lớp 8: Tìm x
1, x(1-2x)+(x-2)(2x-3)=0
2, (x-1)(x+2)-x-2=0
3, x^3-16x=0
4, (2x-3)^2+(x-3)(3-2x)=0

1. Giải đáp:
1)S={1}
2) S={±2}
3) S={0;±4}
4)S={0;3/2}
Lời giải và giải thích chi tiết:
⇔1, x(1-2x)+(x-2)(2x-3)=0
⇔x-2x^2 + 2x^2-3x-4x+6=0
⇔6-6x=0
⇔x=1
Vậy S={1}
2, (x-1)(x+2)-x-2=0
(x-1)(x+2) – (x+2) =0
(x+2) (x-1-1)=0
(x+2)(x-2)=0
⇔$$\left[ \begin{array}{l}x+2=0\\x-2=0\end{array} \right.$$
⇔$$\left[ \begin{array}{l}x=-2\\x=2\end{array} \right.$$
Vậy S={±2}
3, x^3-16x=0
⇔x(x^2-16)=0
⇔x(x-4)(x+4)=0
⇔$$\left[ \begin{array}{l}x=0\\x-4=0\\x+4=0\end{array} \right.$$
⇔$$\left[ \begin{array}{l}x=0\\x=±4\end{array} \right.$$
Vậy S={0;±4}
4, (2x-3)^2+(x-3)(3-2x)=0
⇔(2x-3)^2 – (x-3)(2x-3)=0
⇔(2x-3)(2x-3-x+3)=0
⇔x(2x-3)=0
⇔$$\left[ \begin{array}{l}x=0\\2x-3=0\end{array} \right.$$
$$\left[ \begin{array}{l}x=0\\x=\dfrac{3}{2} \end{array} \right.$$
Vậy S={0;3/2}

2. Giải đáp:

Lời giải và giải thích chi tiết:
1)
$x(1-2x)+(x-2)(2x-3)=0$
$x – 2x² + 2x² – 7x + 6 = 0$
$-6x + 6 = 0$
$6x = 6$
$x = 1$
2)
$(x-1)(x+2) – x – 2 = 0$
$(x-1)(x+2) – (x+2) = 0$
$(x+2)(x-1-1) = 0$
$(x+2)(x-2) = 0$
$x² – 4 = 0$
$x² = 4$
$x = ±2$
3, $x³-16x=0$
$x(x² – 16) = 0$
$$\left[ \begin{array}{l}x=0\\x²=16\end{array} \right.$$
⇒ $$\left[ \begin{array}{l}x=0\\x=±4\end{array} \right.$$
4, $(2x-3)²+(x-3)(3-2x)=0$
$(2x – 3)² – (x-3)(2x-3) = 0$
$(2x-3)(2x – 3 -x + 3) = 0$
$(2x – 3)x = 0$
$$\left[ \begin{array}{l}x=0\\x=\dfrac{3}{2}\end{array} \right.$$